e-procurement and transparency in public sector : a case of Local Government Engineering Department (LGED), Dhamoirhat upazila,Naogaon. - Ahmed, Hussain (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.